Implementasi Metode QINQ Pada Jaringan Metro Ethernet Untuk Memaksimalkan Penggunaan VLAN Menggunakan Teknologi GPON Studi Kasus : PT. Telkom Indonesia - Prayoga Pangestu; Yusuf, Raka (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
VLAN is part of network system that serves as the divider, The use of vlan very helpful in mapping the router or switch on the device. The use of vlan become a sure thing in building architecture of effective and flexible. Not except one of a company service providers like PT. Telkom Indonesia. The use of vlan according to the standard of limited to specification 802.1q with the limited to 1 – 4096 VLAN ID can be used. This will make a problem when found vlan id who have been used for a network will not get used again to another network. The problem also can be found on PT Telkom Indonesia who uses GPON (Gigabit Passive Optical Network) to meet the needs of their customers. Based on the problems encountered , researchers want to use of vlan qinq on technology GPON (Gigabit Passive Optical Network) To solve the problem limited vlan id that might be encountered when meet the needs of from customers PT. Telkom Indonesia .